The Burden of Obesity in Saudi Arabia: A Real-World Cost-of-Illness Study - Nagi MA; Almalki ZS; Thavorncharoensap M; Sangroongruangsri S; Turongkaravee S; Chaikledkaew U; Alqahtani AM; AlSharif LS; Alsubaihi IA; Alzarea AI; Alsultan MM (ClinicoEconomics and Outcomes Research)
Mouaddh Abdulmalik Nagi,1,2 Ziyad Saeed Almalki,3,* Montarat Thavorncharoensap,4,5,* Sermsiri Sangroongruangsri,4 Saowalak Turongkaravee,4 Usa Chaikledkaew,4,5 Abdulhadi M Alqahtani,6 Lamis S AlSharif,6 Ibrahim A Alsubaihi,7 Abdulaziz I Alzarea,8 Mohammed M Alsultan9 1Doctor of Philosophy Program in Social, Economic, and Administrative Pharmacy, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 2Department of Pharmacy, Faculty of Medical Sciences, Aljanad University for Science and Technology, Taiz, Yemen; 3Department of Clinical Pharmacy, Prince Sattam bin Abdulaziz University, Riyadh - Al-Kharj, Saudi Arabia; 4Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, Thailand; 5Mahidol University Health Technology Assessment (MUHTA) Graduate Program, Mahidol University, Bangkok, Thailand; 6Clinical Research Department, Research Center, King Fahad Medical City, Riyadh, Saudi Arabia; 7Department of Clinical Trials Support and Development, Saudi National Institute of Health, Riyadh, Saudi Arabia; 8Department of Clinical Pharmacy, Al-Jouf University College of Pharmacy, Sakaka, Saudi Arabia; 9Department of Pharmacy Practice, College of Clinical Pharmacy, Imam Abdulrahman bin Faisal University, Dammam, Saudi Arabia*These authors contributed equally to this workCorrespondence: Ziyad Saeed Almalki, Department of Clinical Pharmacy, Prince Sattam bin Abdulaziz University, P.O. Box: 173, Riyadh - Al-Kharj, 11942, Saudi Arabia, Email z.almalki@psau.edu.sa Montarat Thavorncharoensap, Department of Pharmacy, Faculty of Pharmacy, Mahidol University, Bangkok, 10400, Thailand, Email montarat.tha@mahidol.ac.thBackground: The rising prevalence of obesity in the Kingdom of Saudi Arabia (KSA) poses a significant public health challenge. Estimates of the economic cost of obesity are crucial for prioritizing healthcare interventions, guiding policy choices, and justifying budget allocations aimed at reducing obesity prevalence. This study aimed to estimate the cost of obesity in the KSA in 2022.Methods: A prevalence-based cost-of-illness approach was used to determine the cost of obesity. This analysis encompasses 29 diseases, namely obesity and twenty-eight diseases attributable to obesity. Both direct and indirect costs were considered. The annual cost of treatment for each obesity-attributable disease was obtained from the hospital records of one tertiary hospital in the KSA. Data on direct non-medical costs were obtained from the patient survey. The human capital approach was used to estimate the indirect costs of morbidity and mortality.Results: The total economic burden of obesity (2022 values) was estimated at US$116.85 billion from a societal perspective and US$109.67 billion from a healthcare system perspective. From a societal perspective, the total direct medical cost accounted for the largest portion of the total cost (94%). In terms of direct medical costs, the cost of treating diseases attributable to obesity was substantially greater than the cost of treating obesity itself. According to the sensitivity analysis, the total cost ranged from 3.4% of the country’s Gross domestic product (GDP) when the unit cost of treatment was reduced by 74% to 9.5% of the country’s GDP when the prevalence of obesity and its comorbidities was reduced by 5%.Conclusion: Obesity imposes a substantial economic burden on the healthcare system and society in the KSA. Interventions aimed at promoting healthier lifestyles to reduce the prevalence and incidence of obesity and its comorbidities are highly warranted to alleviate the impact of obesity in the country.Keywords: body mass index, cost-of-illness, economic burden, obesity, Saudi Arabia